Analysis of green IT challenges for Macedonian companies - Gavrilovska, Daniela; Zdraveski, Vladimir; Trajanov, Dimitar (IEEE, 2013)
The Green IT concepts, very popular among large companies worldwide, seems to have many obstacles in some areas/communities, despite the possibility of saving money. The contribution of this paper to the scientific discussion of Green IT is based on the research done among Macedonian companies and we comment on the challenges they are faced with in implementing Green IT concepts and we introduce a few recommendations for next steps.
Keywords: benefits, Green IT, obstacles, profit